Sediment organic carbon stocks in tropical lakes and its implication for sustainable lake management - T.R. Soeprobowti; N.D. Takarina; P.S. Komala; L. Subehi; M. Wojewódka-Przybył; J. Jumari; R. Nastuti (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The lakeside has an enormous sediment carbon storage potential; however, it is susceptible to various environmental changes and can easily become a source of carbon emissions. Understanding the amount of carbon storage in lakeside sediments and organic matter sources may provide information about the potential of lakeside zones in climate change mitigation, particularly for sustainable lake management. This study aims to estimate sediment organic carbon stock and the sources of organic matter in the Maninjau Lakeside-West Sumatera, Indonesia.METHODS: Sediment sampling was performed at five research sites, with a depth of 0–100 centimeters. Sediment samples were divided into 4 subsamples: 0–15; 15–30; 30–50; and 50–100 centimeters. Bulk density and total nitrogen content were analyzed, and the percentage of organic carbon was calculated from the loss of ignition. The sediment organic carbon stock was calculated based on the bulk density and organic carbon content. Carbon per nitrogen ratio was also calculated to determine temporal changes in the sources of organic matter in the lake.FINDINGS: This study demonstrated that Maninjau Lakeside has an enormous potential sedimentary organic carbon stock range between 284.23–442.59 megagrams per carbon per hectare. The highest total sediment carbon stock was found in Duo Koto (442.59 megagrams per carbon per hectare), with the lowest in Koto Kaciak (284.23 megagrams per carbon per hectare). In addition, the study’s results also exhibited significant differences in sediment organic carbon stocks at each location with different land use and cover; in this case, the forest area has a higher carbon stock value than the agricultural and settlement areas. Therefore, it is essential to take initiatives for the restoration and conservation of lakeside areas because of their essential role in mitigating the climate change. The mean ratio of organic carbon and total nitrogen was between 9.96 to 16.91, indicating that phytoplankton, a mixture of floating macrophytes, and submerged vegetation were the sources of organic matter.CONCLUSION: In general, the value of sediment organic carbon stocks tends to be lower in locations with intensive agricultural settlements than in forest areas. This study emphasizes that restoring lakeside wetland is vital in increasing sediment organic carbon stocks and maintaining lake sustainability.